(untitled) (Revista Brasileira Multidisciplinar, 2021)
Photobiomodulatory effects of low-intensity laser radiation (LILR) in cells cultured in standard, two-dimensional conditions are well established. Conversely, the characteristics of this effect in three-dimensional (3D) cultures, which are currently recommended due to the greater similarity with cellular behavior in vivo, have not yet been widely investigated. The objective of this work was to analyze the biomodulator effect of LILR, on the wavelength (λ) of 685 nm, on the constitution process and on the viability of cells cultured as multicellular spheroid (MSs). For this, agarose molds containing microwells were seeded (2x105 cell/ml) with osteogenic precursor cells (OPCs - MC3T3-E1) and kept under ideal culture conditions. The molds were irradiated for five consecutive days with doses of 0.5, 1.0 and 1.5 J/cm², the first irradiation being performed immediately after sowing. The process of constitution of MSs was analyzed and the cultures were submitted to the cell viability test. The results demonstrated that the LILR at λ 685 nm exerted a dose-dependent biomodulatory effect on cell metabolism and on the process of constituting the MSs of OPCs. These results demonstrate the potential of photobiomodulation to contribute to the process of constituting MSs, which can be explored in the strategies of multicellular spheroids therapy used in regenerative medicine and bioprinting.